Perceptions on censervation measures for sustainable environmental resource use in Langkawi Island - Wahid, Mohamad Faiz (2018)
The development of sustainable tourism is very important in preserving the ecotourism area in order for it to survive from the one generation to another. Langkawi Island, Kedah is rich with its biodiversity make this area as one of the popular tourism attractions among the locals and foreigners. As a result, the perception on conservation measure will affect local residents who were in the vicinity. The objective of this research was to understand perceptions on conservation measures that ensure sustainability of environmental resources in Langkawi. It will included the examination on issues including (i) litter pollution, (ii) sea water quality, (iii) control of eagle feeding and (iv) removal of fossil & endangered plants and animal. Non-parametric tests of correlation analysis were used in this study to identify the strength of the relationship between socio-demographic variables of the respondents (i.e. local community and tourists) with their perceptions on environmental conservation measures. Four socio-demographic variables were identified statistically significant with environmental challenges. It includes the age of the respondents, number of children, education level and their monthly income. In this study, to control litter pollution the respondents considered that the concept of recycling should be fully practiced in Langkawi Island. They also observed that fossil and endangered plants and animals’ removal by tourists has a negative impact on the natural ecosystem of Kilim Geoforest Park (KGP). Apart from that, the respondents also recognize that conservation measure is important to control water quality while the enforcement measures should be fully practiced in Langkawi Island to control eagle feeding activity and stop fossil and endangered plants and animals’ removal in KGP. The results of this study provide current information that could be used by the management agencies in Langkawi Island including local authorities such as LADA and KGP, and other non-governmental agencies (NGOs) to sustainably develop tourism activities and to conserve environmental resource in Langkawi Island.